What factors can influence the reproductive phenology of neotropical piper species (Piperaceae) in a semi-deciduous seasonal forest? - Valentin-Silva, Adriano [UNESP] (2018)
Plant phenophases can be modulated by abiotic factors as well as by evolutionary history. We tested the influence of factors shaping the reproductive phenology of 17 co-occurring Piper species in a semi-deciduous seasonal forest in southeastern Brazil over a 12 month period. We describe the phenology, applying circular statistics to the flowering and fruiting phenophases for each species. Mantel correlation tests were conducted to investigate the role of phylogeny in phenological responses, and the influence of abiotic variables (temperature, rainfall, and day length) was analyzed using generalized linear models. Additionally, we tested whether the presence of latent flower buds influenced flowering and fruiting times. The phenological variation across species of Piper in the reproductive stages was not phylogenetically structured. Flowering and fruiting occurred throughout the year, but higher seasonality was detected in the flowering phase, which positively correlated with long days (~13 h). The flowering phase was shorter and occurred earlier in Piper species with latent flower buds than in species without them, probably because these species are better adjusted to respond when climate conditions are favorable for flower anthesis. Thus, abiotic factors and the presence of latent flower buds shape the reproductive phenology of Piper species.